On the Structure of Specialized Norms of Contemporary Russian Law - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This article examines theoretical issues related to specialized norms of modern Russian law. The author determines their status, types, provides a reasoned author's position on the issue of their structure, which is closest to the structure of regulatory norms of law, but has specific features. Among the specialized norms of law, conflict norms, consisting of a hypothesis and a disposition, stand out.